Analisis Pengendalian Kualitas (Quality Control) Guna Meningkatkan Kualitas Produk Kosmetik PT Fanbo. - Sitorus, Santa Lusianna; Nisa, Roihatun; Basuki, Sucipto (Jurnal Bisnis Manajemen dan Akuntansi, 2024)
ABSTRAK The cosmetics business in Indonesia is growing very rapidly in line with the increase in people's living standards and purchasing power. This creates tight competition in the industry. Therefore, in order for a company to survive and win in business competition, the company must be able to maintain and improve the quality of the products it produces. Good product quality is produced by carrying out routine quality control analysis activities. The aim of this research is to analyze the quality control of PT Fambo cosmetic products. This research method uses a descriptive research design, with a qualitative approach. Research analysis was carried out before entering the field, while in the field and after finishing in the field. The results of the research show that the implementation of quality control to improve the quality of PT Fanbo's cosmetic products has been carried out carefully and in detail in accordance with the Company's Operational Standards, the company also implements comprehensive quality control methods so that PT Fanbo has succeeded in creating cosmetic products that meet the highest quality standards, providing benefits for consumers, and remain competitive in a competitive market.